When social movements fail or succeed: social psychological consequences of a collective action’s outcome - Carvacho, Héctor; González, Roberto; Cheyre, Manuel; Rocha, Carolina; Cornejo, Marcela; Jiménez-Moya, Gloria; Manzi, Jorge; Álvarez-Dezerega, Catalina; Álvarez, Belén; Castro, Diego; Varela, Micaela; Valdenegro, Daniel; et al. (Frontiers in Psychology, 2023)
Collective actions occur all around the world and, in the last few years, even more frequently. Previous literature has mainly focused on the antecedents of collective actions, but less attention has been given to the consequences of participating in collective action. Moreover, it is still an open question how the consequences of collective action might differ, depending on whether the actions are perceived to succeed or fail. In two studies we seek to address this gap using innovative experimental studies. In Study 1 (N = 368) we manipulated the perceptions of success and failure of a collective action in the context of a real social movement, the Chilean student movement from last decade. In Study 2 (N = 169), in addition to manipulating the outcome, we manipulated actual participation–using a mock environmental organization aiming to create awareness in authorities–to test the causal effect of both participation and success/failure on empowerment, group efficacy, and intentions of future involvement in normative and non–normative collective actions. Results show that current and past participation predict overall participation in the future, however, in Study 2 the manipulated participation was associated with having less intentions of participating in the future. In both studies, perception of success increases group efficacy. In Study 1, we found that when facing failure, participants increase their willingness to participate more in the future as opposed to non-participants that actually decrease theirs. In Study 2, however, failure increases the perception of efficacy for those with a history of non-normative participation. Altogether these results highlight the moderating role of the outcome of collective action to understand the effect of participation on future participation. We discuss these results in light of the methodological innovation and the real world setting in which our studies were conducted.